Assessment of Wind Power Potential at the Chittagong Coastline in Bangladesh (Dhaka University Journal of Science, 2019)
A small wind data logger is used to record the wind speed for one year (2015 to 2016) at the Chittagong coastline in Bangladesh. A multi-storied building’s rooftop in Chittagong Export Processing Zone (CEPZ) is selected as a wind data collection site. The recorded data is analyzed using Weibull distribution functions. Three statistical methods are used to find and compare the Weibull parameters. Weibull probability density function and cumulative distribution are used to explain the recorded data. The analysis shows the shape factor of the site is 1.8 and the yearly scale factor is 2.2ms-1. The highest values of these parameters are found by calculation in the month of June when the maximum shape factor is 3 and the maximum yearly scale factor is 3.95 ms-1. To estimate yearly energy production three different wind turbine models ‘Aventa AV-7’, ‘Enercon E-33’ and ‘Enercon E-53’ are used and the estimation is done using a mathematical approach. The probable wind power production capacity of this site would be around 5457kWh per year and the energy density of this site would be around 11.54 kWhm-2. This research work may be helpful for the design and planning of any wind power plant at the Chittagong coastline area in Bangladesh.Dhaka Univ. J. Sci. 67(1): 27-32, 2019 (January)